Predicting Outcome in Acute Severe Colitis—Controversies in Clinical Practice in 2021. (3rd January 2021) - Gupta, Vipin; Mohsen, Waled; Chapman, Thomas P; Satsangi, Jack
Abstract: Acute severe ulcerative colitis [ASUC] remains a common medical emergency, with 25% of patients with ulcerative colitis experiencing at least one event in their disease course. Despite advances in medical therapy, ASUC continues to be associated with considerable morbidity and mortality, with up to 30% of patients requiring colectomy during initial admission. Our aim was to review the current controversies and recent progress in risk stratification, prediction of outcome, and personalisation of care in ASUC. We re-assess the use of Truelove and Witts' criteria, serum biomarkers, and the use of composite clinical indices in current clinical practice. We explore the potential for endoscopic prediction using defined validated indices for accurate and early prognostication, and the need to define outcome. We also consider the impact of the current COVID-19 pandemic. Finally, we discuss the current research agenda, including the application of new and emerging biomarkers coupled with multi-omics and the implications in management and optimisation of outcome. Research priorities for the prediction of outcome in acute severe colitis include the following. 1. Development of an accurate admission score to guide early medical rescue therapy or colectomy. 2. Utility of point-of-care faecal calprotectin, with determination of optimal cut-off values. 3. Role of serum and faecal infliximab levels to both predict outcome and guide accelerated infliximab dosing. 4. Role of novel biomarkers, including serum calprotectin, in predicting response to corticosteroids or rescue therapy. 5. Specific predictors of response to ciclosporin and infliximab to allow rationalisation of drug use. 6. Utility of validated endoscopic scores. 7. Utility of radiological assessment beyond use of plain abdominal X-ray. 8. The use of multiomics and machine learning to predict risk of Acute Severe Colitis in patients with Ulcerative Colitis.